Cellular and Extracellular Components in Tumor Microenvironment and Their Application in Early Diagnosis of Cancers - Rui Wei; Si Liu; Shutian Zhang; Li Min; Shengtao Zhu (Analytical Cellular Pathology)
Tumors are surrounded by complex environmental components, including blood and lymph vessels, fibroblasts, endothelial cells, immune cells, cytokines, extracellular vesicles, and extracellular matrix. All the stromal components together with the tumor cells form the tumor microenvironment (TME). In addition, extracellular physical and chemical factors, including extracellular pH, hypoxia, elevated interstitial fluid pressure, and fibrosis, are closely associated with tumor progression, metastasis, immunosuppression, and drug resistance. Cellular and extracellular components in TME contribute to nearly all procedures of carcinogenesis. By summarizing the recent work in this field, we make a comprehensive review on the role of cellular and extracellular components in the process of carcinogenesis and their potential application in early diagnosis of cancer. We hope that a systematic review of the diverse aspects of TME will help both research scientists and clinicians in this field.